Port Authorities as Urban Land Developers: The Case of the Toronto Harbour Commissioners and Their Outer Harbour Project, 1912-68 - Merrens, Roy (Urban History Review / Revue d'histoire urbaine, 1988)
Port authorities have been important presences in Canada's port cities, playing major roles in determining the physical form and land-use functions of urban waterfront lands. Their formative roles warrant attention from scholars concerned with the city-building process in Canada. This study focuses upon one such body, The Toronto Harbour Commissioners, and how and why it has functioned as a land development agency. An analysis of the commissions Outer Harbour project between 1912 and 1968 shows the commissions central concern with land development: ostensibly presented as a harbour facility, the project was actually intended to be a key component in the commissions proposed redevelopment of Toronto's central waterfront for profitable commercial and residential use. The project also reveals the significance of landfilling in the commissions urban development role, and, incidentally, explains the existence of the three-mile artificial headland projecting out into Lake Ontario from Toronto's waterfront. The role of the commission as a development agency is explained in terms of its original 1911 mandate, which in turn reflects the intentions of the Toronto Board of Trade, the body that had led the drive to create the commission.